A Bibliometric Review of Soft Skills: Understanding the Trajectories and Research Agenda - Costa, Marcelle Feitoza Bassi (2025)
Soft skills have become a crucial interdisciplinary research focus, underscoring the growing relevance of intrapersonal and interpersonal dimensions in today’s world. This study systematically maps and analyzes the academic literature on soft skills across leading journals, identifying trends, research gaps, key authors, and focal areas. The study addresses three research questions using bibliometric methods: (a) What is the publication timeline for soft skills? (b) Which countries, journals, and authors lead in publishing soft skills research? (c) What are the main disciplines, research topics, and most-cited articles in this field? Findings highlight a notable increase in publications since 2013, with social sciences dominating the field, followed by engineering and technology. The research primarily centers on higher education and the labor market, with the most cited studies emphasizing the importance of soft skills for employability and revealing discrepancies between students’ perceptions and employer expectations. This disconnect underscores the need for stronger alignment between education systems and labor market requirements. This study provides a comprehensive foundation for understanding the landscape of soft skills research, offering valuable insights to guide future investigations and inform policies and practices in education and the labor market.